The Effect of Intellectual Intelligence (IQ), Emotional Intelligence (EQ), and Spiritual Intelligence (SQ) on The Performance of Regional Leaders Division II BPJS Health Commitment With Variable In Mediation - Pambudi, Aditya Rioko; Hendriani, Susi; Efni, Yulia (Program Pascasarjana, Universitas Riau, 2018)
This study aims to Determine and analyze the influence between Intellectual Intelligence (IQ), Emotional Intelligence (EQ), and Spiritual Intelligence (SQ) on the Performance of BPJS Health Division II Regional Leaders With Variable Commitment As Mediation. The population of this study were all leaders in BPJS Health Division II with the level of manager and assistant manager who totaled 121 people. The sample in this study were 121 people Obtained by the method of sampling census. The instrument used for the data collection is by ordinal scale model questionnaire. To test the hypothesis used descriptive analysis and PLS analysis.The results of the data analysis show that (1) Intellectual Intelligence (IQ) has a negative and significant effect on performance, (2) Commitment is not a mediation variable between intellectual intelligence (IQ) to leadership performance, (3) Emotional Intelligence (EQ ) has positive and significant (4) Commitment is the perfect mediation variable between emotional intelligence (EQ) on the performance of leadership, (5) Spiritual intelligence (SQ) has no significant negative effect on performance, (6) Commitment is the perfect mediation variable between spiritual intelligence (SQ) on leadership performance, and (7) Commitment has a negative and significant effect on performance